Experimental study on the effect of codirectional Raman gain on system's performance - Kim, Chul Han; Son, Eui Seung; Cho, Ho-Shin; Han, Young-Geun; Lee, Ju Han; Lee, Sang Bae (OPTICAL SOC AMER, 2007)
We have experimentally investigated the impact of codirectional Raman gains on the performance of distributed fiber Raman amplified systems. The effects of various noise sources, such as optical signal-to-noise ratio (OSNR) degradation, fiber nonlinearities and surviving channel gain variation in different Raman pumping schemes, were evaluated as a function of input power into a fiber span. For measurements, distributed Raman gain was generated by pumping the fiber span with different combinations of Raman pump power between co- and counterdirections. From the results, we found that a large counterdirectional Raman gain assisted by a small codirectional gain could improve the overall static and dynamic performance of distributed Raman amplified systems. (C) 2007 Optical Society of America.